Impurities in semiconductors : - Fistul, Victor I. (CRC Press, 2004)
This work explores the behavior of impurity atoms in semiconductors, integrating experimental data with theoretical interpretation. It presents the current literature on the state and behavior of impurities in semiconductors, and explains the basic physics of hydrogen-like impurities to help readers understand the properties imparted by these impurities. The book also analyzes the macroscopic and microscopic mechanisms of the solubility and migration of impurities and defects in the crystal lattice, and presents a systematic analysis of different effects resulting from the interactions between impurities and other defects in crystal lattices. Author information is not given